HIGH-DOSE ORAL VITAMIN C WITH MINIMAL TOPICAL BETAMETHASONE IN THE MANAGEMENT OF MILD POMPHOLYX ECZEMA: A CASE REPORT - Ali, Asif (Journal of Ayub Medical College Abbottabad, 2026)
Background: Pompholyx eczema presents as vesicular skin eruptions in hands and feet and follows a chronic and relapsing disease course. While topical corticosteroids are routinely used for treatment, long-term use remains a major concern. Vitamin C is known for its role in immunity and wound healing. However, it has not been widely investigated in pompholyx eczema. Case Presentation: We report the clinical case of a 45-year-old Pakistani male with a 22-year history of mild pompholyx eczema. Eczematous flares in this patient are associated with the use of medicated soaps, dishwash detergents and dryness induced by water. Interestingly, during the COVID-19 pandemic, he began taking high-dose oral vitamin C (2000 mg/day). This coincided with a significant reduction in symptoms. The patient was inspired by this improvement and designed a self-directed observational trial in consultation with a dermatologist. He started with one self-inflicted active lesion after using dishwash detergent. He started using 2000 mg/day vitamin C for 8 days and only single nightly dose of topical 0.1% betamethasone on day 6 and 7. This led to complete resolution of the lesion on day 9 and the patient documented the healing process photographically. Conclusion: The adjunctive role of vitamin C has the potential to reduce corticosteroid dependence in Pompholyx eczema management. However, further clinical research is warranted to explore the clinical efficacy of vitamin C in eczema.